The Assessment and Mapping of Sulphate Concentration in Drainage Along Taman Melewar, Parit Raja, Batu Pahat - RAZAK, RAZERIM; DR.MOHD HAIRUL BIN KHAMIDUN, (Recent Trends in Civil Engineering and Built Environment, 2023)
Rapid industrialization and overpopulation have stimulated increase in waste water both domestic and industrial which increases the amount of sulphate discharge into the drainage systems then affect to the environment. The study was to identify the characteristic of drainage water along Taman Melewar. The laboratory testing was carried out based on selected parameters which are pH, DO, TSS, turbidity and sulphate. The application of spatial mapping using Surfer 16 software to identify the sulphate concentration clearly. Water samples were collected from the drains during dry and after rainy day at various points. The results for each parameter i.e pH ranged 2.79 – 2.91, dissolved oxygen ranged 2.3 mg/L – 7.34 mg/L, turbidity ranged 4.31–6.5 NTU, total suspended solid ranged 5 mg/L – 30 mg/L and Sulphate ranged 110 mg/L – 138 mg/L. The mapping of sulphate concentration for dry day and wet day condition showed a different pattern in distribution of the sulphate along the water body. The location to be threatened to pollution was Station 4. In order to execute the improvisation on the water quality management, an improvising recommendation of water quality is determined.